Miscellanea Miridologica (Insecta: Heteroptera) - Schwartz, Michael D.; Chérot, Frédéric (Zootaxa, 2005)
Eurotas Distant, 1884 is transferred from Mirinae, Mirini to Orthotylinae, Orthotylini (new subfamily placement) and Femurocoris Carvalho, 1977 is transferred from Mirinae, Mirini to Deraeocorinae, Hyaliodini (new subfamily placement). The following new combinations are suggested: Apolygus biannulatus (Poppius, 1915) comb. n. [Lygus], Apolygus bruneinensis (Carvalho, 1980) comb. n. [Lygus], Apolygus longirostris (Poppius, 1914) comb. n. [Lygus], Apolygus umbratus (Poppius, 1914) comb. n. [Lygus], Guisardinus lineatus (Carvalho in Carvalho & Gross, 1979) comb. n. [Chrysorrhanis], Gutrida mocquerysi (Poppius, 1912) comb. n. [Lygus], Lampethusa attenuata (Distant, 1883). comb. n. [Taedia], Lygidolon vittatum (Reuter, 1903) comb. n. [Lygus], Lygocoris viridiflavus (Poppius, 1914) comb. n. [Lygus], Lygocoris vittulatus (Poppius, 1914) comb. n. [Lygus], Neolygus indicus (Poppius, 1914) comb. nov. [Lygus], Neolygus sondaicus (Poppius, 1914) [Lygus], Pleurochilophorus sexlineatus (Delattre, 1949) n. comb. [Corizidolon], Sabactiopus laevipennis (Poppius, 1914) comb. n. [Lygus], Sabactiopus sublaevis (Poppius, 1914) comb. n. [Lygus], Sabactus exiguus (Poppius, 1914) comb. n. [Lygus], Schoutedenomiris schmitzi (Chérot, 1996) comb. n. [Trigonotylus], and Taylorilygus oceanicus (Poppius, 1914) comb. n. [Lygus]. Lectotypes are designated for Corizidolon sexlineatum Delattre, 1949, Lygus exiguus Poppius, 1914, Lygus indicus Poppius, 1914, Lygus laevipennis Poppius, 1914, Lygus nebulosus Poppius, 1914, Lygus oceanicus Poppius, 1914, Lygus sondaicus Poppius, 1914, Lygus vittatus Reuter, 1903, and Miris cruentatus Brullé, 1832. Two replacement names – Tropidosteptes costai Schwartz & Chérot (nomen novum) and Phytocoris garyi Schwartz & Chérot (nomen novum) – are given respectively to Tropidosteptes scutellatus Carvalho & Costa, 1993 nec Tropidosteptes scutellatus Distant, 1893 and Phytocoris falcatus Stonedahl, 1995 nec Phytocoris falcatus Linnavuori, 1984. The following taxa are raised to species level: Neostenotus confluentus Carvalho & Fontes, 1972 stat. n., Neostenotus itatiaianus Carvalho & Fontes, 1972 stat. n., Neostenotus serranus Carvalho & Fontes, 1972 stat. n., Neostenotus similimus Carvalho & Fontes, 1972 stat. n., Neostenotus sulinus Carvalho & Fontes, 1972 stat. n., Poeas alvarengai Carvalho, 1975 stat. n., Poeas atlantica Carvalho, 1975 stat. n, Poeas caatinga Carvalho, 1975 stat. n., Poeas chapada Carvalho, 1975 stat. n., and Poeas2© 2005 Magnolia Presscipoa Carvalho, 1975 stat. n. The subgeneric classification of Hyalopeplus cuneatus Carvalho in Carvalho & Gross, 1979 is discussed.